Respuesta :

gmany

Answer:

[tex]\large\boxed{A==\dfrac{3-\sqrt6}{12}\ cm^2}[/tex]

Step-by-step explanation:

The shaded region is the triangle with base b and height h.

[tex]b=BD-CD\to b=\dfrac{\sqrt2}{2}-\dfrac{\sqrt3}{3}=\dfrac{3\sqrt2}{(2)(3)}-\dfrac{2\sqrt3}{(2)(3)}=\dfrac{3\sqrt2-2\sqrt3}{6}\\\\h=AD\to h=\dfrac{\sqrt2}{2}[/tex]

The formula of an area of a triangle:

[tex]A=\dfrac{bh}{2}[/tex]

Substitute:

[tex]A=\dfrac{\frac{3\sqrt2-2\sqrt3}{6}\cdot\frac{\sqrt2}{2}}{2}=\left(\dfrac{3\sqrt2-2\sqrt3}{6}\right)\left(\dfrac{\sqrt2}{2}\right)\left(\dfrac{1}{2}\right)\\\\\text{use the distributive property}\ a(b+c)=ab+ac\\\\=\dfrac{(3\sqrt2-2\sqrt3)(\sqrt2)}{(6)(2)(2)}=\dfrac{(3\sqrt2)(\sqrt2)-(2\sqrt3)(\sqrt2)}{24}\\\\\text{use}\ \sqrt{a}\cdot\sqrt{a}=a\ \text{and}\ \sqrt{ab}=\sqrt{a}\cdot\sqrt{b}\\\\=\dfrac{(3)(2)-2\sqrt6}{24}=\dfrac{2(3-\sqrt6)}{24}=\dfrac{3-\sqrt6}{12}[/tex]

Answer:

see explanation

Step-by-step explanation:

The area of the shaded triangle = area of ΔABD - area of ΔADC

A of ΔABD = [tex]\frac{1}{2}[/tex] × AD × BD

A = [tex]\frac{1}{2}[/tex] × [tex]\frac{\sqrt{2} }{2}[/tex] × [tex]\frac{\sqrt{2} }{2}[/tex]

   = [tex]\frac{2}{8}[/tex] = [tex]\frac{1}{4}[/tex]

--------------------------------------------------------------------------

A of ΔACD = [tex]\frac{1}{2}[/tex] × AD × DC

A = [tex]\frac{1}{2}[/tex] × [tex]\frac{\sqrt{2} }{2}[/tex] × [tex]\frac{\sqrt{3} }{3}[/tex]

A = [tex]\frac{\sqrt{6} }{12}[/tex]

-------------------------------------------------------------------------

shaded area = [tex]\frac{1}{4}[/tex] - [tex]\frac{\sqrt{6} }{12}[/tex]

               

= [tex]\frac{3}{12}[/tex] - [tex]\frac{\sqrt{6} }{12}[/tex] = [tex]\frac{3-\sqrt{6} }{12}[/tex]

ACCESS MORE